Insights into the mechanics of en-échelon sigmoidal vein formation using ultra-high resolution photogrammetry and computed tomography. (August 2015) - Thiele, Samuel T.; Micklethwaite, Steven; Bourke, Paul; Verrall, Michael; Kovesi, Peter
Abstract: Two novel techniques, photo based reconstruction (photogrammetry) and computed tomography (CT), are used to investigate the formation of an exceptional array of sigmoidal veins in a hand sample from Cape Liptrap, Southern Victoria, and to provide constraint on models for their development. The accuracies of the photogrammetric models were tested by comparison with a laser scan generated three dimensional (3D) model. The photogrammetric model was found to be accurate to at least 0.25 mm and substantially more detailed than the laser scan. A methodology was developed by which 3D structural measurements could be extracted from the photogrammetric model. This was augmented with the CT model which, through its capacity to elucidate internal structure, was used to constrain the geometry and linkage of structures within the rock volume. The photogrammetric and CT data were then combined with detailed photomicrographs to evaluate the evolution of the sigmoidal veins in the sample. The angle between the sigmoidal vein margins and an inferred shear zone, as well as the orientations of the crystal fibres, were found to imply a rotation of >27°. However coeval pressure solution seams and older veinlets in the rock bridges between the veins were only found to have rotated by ∼10°, an observation not easily explained using existing models for sigmoidal vein formation. A new model is proposed in which a significant component of sigmoidal vein geometry is due to localised dilation caused by slip on the pressure solution seams. The process involves strain partitioning onto pressure solution seams, which leads to exaggeration of sigmoidal vein geometries. If not accounted for, the apparent vein rotation due to slip partitioning introduces errors into calculations of simple shear and volume strain based on sigmoidal arrays of this type. Furthermore, the CT data demonstrated that in 3D the veins are continuous and channel-like, implying a far higher degree of connectivity and fluid transport than is suggested by their 2D form. Highlights: Photogrammetry is used to construct an accurate textured mesh of a hand sample. 3D structural orientations are extracted to investigate sigmoidal vein formation. Vein geometry appears to be greatly affected by pressure solution mechanisms. 3D analysis shows greater connectivity between veins than their 2D form suggests.